Important Strategies to Achieve Self-Sufficiency in Meat-Poultry in Baghlan Province - Mazlumyar, Sayed Ahmad; Naiemi, Moienuddin (Journal of Natural Sciences – Kabul University, 2024)
Nowadays, the low level of family income, the high price of other meats in Baghlan Province's market, and the high fat content of other meats have increased people's demand for chicken meat. Evidence shows that Baghlan Province, with a population of 1,053,000, cannot supply the amount of chicken meat required by its society. Therefore, this research was conducted to identify important strategies for achieving self-sufficiency in chicken meat production in Baghlan Province. The statistical population of this research consisted of 90 individuals, including officials from educational and academic departments, as well as stakeholders in the livestock sector, such as government and private institutions and agricultural and livestock cooperatives in the province. The data collection tool was a questionnaire. After being validated by experts in the field, the questionnaire, including 40 variables, was prepared. Its reliability was assessed using Cronbach's alpha coefficient, which averaged 0.95. The statistical methods employed in this research included descriptive statistics, such as standard deviation and mean, alongside exploratory factor analysis using SPSS 26 software. The findings revealed four key components as crucial strategies for achieving self-sufficiency: reforming the support system, empowering the broiler industry, ensuring the availability of production factors, and employing experts in the poultry industry. The "support system reform" component accounted for 21.32% of the variance. These findings can provide important insights for planning and policymaking in this sector, offering guidance to officials and stakeholders involved in achieving self-sufficiency in chicken meat production.